Specific cell subclusters of dental pulp stem cells respond to distinct pathogens through the ROS pathway - Xu, Tiansong; Liu, Yangjia; Zhang, Wen; Li, Murong; Zhang, Liqi; Li, Xueying; Zhang, Yifei; Yue, Lin; Li, Sha; Lin, Ye; Zou, Xiaoying; Chen, Feng (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMicrobial pathogens invade various human organs, including the oral cavity. Candida albicans (C.a) and Streptococcus mutans (S.m) served respectively as representative oral pathogenic fungi and bacteria to stimulate dental pulp stem cells (DPSCs) and to screen the DPSC subcluster that specifically responded to fungal infection.MethodsDPSCs were obtained from the impacted third molars of six healthy subjects. Then, cells were mixed and divided into three samples, two of which were stimulated with C.a and S.m, respectively; the third sample was exposed to cell medium only (Ctrl). Single-cell mRNA sequencing analysis of treated DPSCs was performed.ResultsDPSCs were composed of four major clusters of which one, DPSC.7, exhibited unique changes compared to those of other subclusters. The DPSC.7 cell percentage of the C.a sample was twice those of the Ctrl and S.m samples. DPSC.7 cells expressed genes associated with the response to reactive oxygen species (ROS) response. DPSC.7 subgroup cells established characteristic aggregation under the stimulation of different pathogens in UMAP. The MAPK/ERK1/2 and NF-κB pathways were up-regulated, DUSP1/5/6 expressions were suppressed, FOS synthesis was activated, the immune-related pathway was induced, and the levels of cytokines, including IL-6 and CCL2, were up-regulated in DPSC.7 cells when stimulated with C.a.ConclusionsOur study analyzed the cellular and molecular properties of DPSCs infected by oral fungi and bacteria with single-cell RNA sequencing. A subcluster of DPSCs responded specifically to infections with different pathogens, activating the MAPK and NF-κB pathways to induce immune responses via the ROS pathway. This suggests novel treatment strategies for fungal infections.